Potentiometric investigation of acid-base equilibria of two new pyrimidine derivatives in various methanol-water media - (:unkn) unknown (SERBIAN CHEMICAL SOC, 2006)
The acid-base properties of 1w-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one (L-1) and 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-thione (L-2) Were investigated potentiometrically at an ionic strength of 0.10 M (LiCl) in 19.8, 33.6 and 55.9 % (v/v) methanol-water mixtures at 25.0 +/- 0.1 degrees C. The apparent dissociation constants (p(s)K(a)) were calculated for the di-protonated form ((LH2+2)-H-1 and (LH2+2)-H-2) of pyrimidine bases, using a software package TITFIT, which were then extrapolated to pure water to derive the dissociation constants in aqueous solution (pA,). The aqueous p), constants were found to be: L-1, pK(a2) = 3.76 and pK(a2) = 6.95; L-2, pK(a1) 3.57 and pK(a2) = 6.90. At pH <= 2.00, the dominant species in solution were the protonated form of the amino group substituted at the I-position, while at a pH around 5.00, they were the protonated form of the pyrimidine ring nitrogen at the 3-position. An effect of intramolecular hydrogen bonding on the p(s)K(a) values was observed with L-1 but not L-2. The effects of molecular structure and solvent medium on the p(s)K(a), values are also discussed.
Keywords: dissociation constant; pK(a); potentiometry; pyrimidine derivatives; protonated amines; nitrogen-protonated pyrimidine bases; intramolecular hydrogen bonding; ORGANIC-SOLVENT MIXTURES; DISSOCIATION-CONSTANTS; OXALYL COMPOUNDS; PH; VALUES